2020
DOI: 10.2478/hepo-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of fireweed (Epilobium angustifolium L.) and bioavailability of ellagitannins. A review

Abstract: SummaryFireweed (Epilobium angustifolium L.) is a well-known medicinal plant traditionally used in the treatment of urogenital diseases, stomach and liver disorders, skin problems, etc. E. angustifolium extracts show anti-androgenic, antiproliferative, cytotoxic, antioxidant, anti-inflammatory, immunomodulatory, and antimicrobial activities. The unique combination of biological properties demonstrated by the results of some studies indicates that fireweed has a positive effect in benign prostatic hyperplasia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…E. angustifolium has been used for a long time in folk medicine as an herb supporting the treatment of skin infections [35]. This plant is characterized by high antioxidant activity and contains many valuable compounds, including phenolic acids [31,41]. It is worth mentioning that these compounds penetrated to human skin from the ethanolic extract of this plant, as we demonstrated in our previous study [42].…”
Section: Discussionmentioning
confidence: 75%
“…E. angustifolium has been used for a long time in folk medicine as an herb supporting the treatment of skin infections [35]. This plant is characterized by high antioxidant activity and contains many valuable compounds, including phenolic acids [31,41]. It is worth mentioning that these compounds penetrated to human skin from the ethanolic extract of this plant, as we demonstrated in our previous study [42].…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, preclinical studies reported anti-inflammatory, antioxidative, anti-proliferative, antimicrobial, analgesic, and antiandrogenic activities of the extract [ 70 , 71 ]. Review articles summarized the biological activities of E. angustifolium, including the above-mentioned ones besides cytotoxic, immunomodulatory, photoprotective, anti-ulcer properties, and emphasizing its importance in BPH treatment and prostate cancer prevention [ 72 , 73 , 74 ]. A recent assessment was also made about the wound healing properties of Epilobium species due to its anti-hyaluronidase, anti-collagenase, and antioxidant activities [ 75 ].…”
Section: Medicinal Plants Widely Used In the Treatment Of Bphmentioning
confidence: 99%
“…In general, polyphenols are thought to be responsible for the effects of Epilobium extracts. Ellagitannins are metabolized by the gut microbiota resulting in anti-inflammatory urolithins [ 72 , 76 ]. Oenothein B, a macrocyclic ellagitannin, seems to be at least one of the major bioactive compounds of Epilobium species due to its antioxidant, anti-inflammatory, enzyme inhibitory, antitumor, antimicrobial, and immunomodulatory activity described in several preclinical studies [ 77 ].…”
Section: Medicinal Plants Widely Used In the Treatment Of Bphmentioning
confidence: 99%
See 2 more Smart Citations